How Socio-Economic Impact Tourism Development in Pandemic COVID-19? Study of Bintan Regency, Indonesia - Fitri Kurnianingsih; Iskandar Zulkarnain; Mahadiansar Mahadiansar (International Journal of Social Science and Religion (IJSSR), 2021)
The socio-economic impact is part of the benchmark for measuring the success of regional development in various sectors, especially tourism in Indonesia. During the Covid 19 pandemic, the tourism sector in Bintan Regency has decreased so that it has an impact on the life and welfare of the community. The purpose of this study is to analyze the socio-economic impacts of the tourism sector in the Bintan Regency before COVID 19 and after the COVID-19 pandemic. The research method used is qualitative with a case study approach and a literature approach which will later be analyzed in depth. The results showed that the socio-economy in the tourism sector during the COVID-19 pandemic in Bintan Regency affected people's living conditions to meet their daily needs and did not prioritize profit. Apart from that, the socio-economy also affects the lifestyle of people who must have the initiative to survive. Other findings need strengthening of stakeholders and new socio-economic needs by preparing the quality of human resources to revive the tourism sector in Bintan Regency.